2010
DOI: 10.2147/oaju.s13370
|View full text |Cite|
|
Sign up to set email alerts
|

Neurotransmitter testing of the urine: a comprehensive analysis

Abstract: This paper analyzes the statistical correlation of urinary serotonin and dopamine data in subjects not suffering from monoamine-secreting tumors such as pheochromocytoma or carcinoid syndrome. Peer-reviewed literature and statistical analyses were searched and monoamine (serotonin and dopamine) assays defined in order to facilitate their proper interpretation. Many research findings in the literature are novel. Baseline assays completed with no monoamine precursors differ from baseline assays performed on a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 12 publications
0
60
0
Order By: Relevance
“…1 Novel statistical results of spot baseline urinary neurotransmitter testing of norepinephrine and epinephrine assays from a database accumulated by two of the authors of this paper are reported here. Urinary norepinephrine and epinephrine samples obtained on different days from the same subject were statistically analyzed using a matchedpairs t-test.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…1 Novel statistical results of spot baseline urinary neurotransmitter testing of norepinephrine and epinephrine assays from a database accumulated by two of the authors of this paper are reported here. Urinary norepinephrine and epinephrine samples obtained on different days from the same subject were statistically analyzed using a matchedpairs t-test.…”
Section: Methodsmentioning
confidence: 98%
“…This supports the assertion that spot urinary dopamine values are not uniform or reproducible from day to day. 1 Results of the four matched-pairs t-tests shown in Table 1 reveal that there are significant differences between spot baseline urinary neurotransmitter testing performed on different days from the same subject for all four monoamines under scrutiny.…”
Section: Spot Baseline Dopamine Matched-pairs T-testmentioning
confidence: 98%
See 3 more Smart Citations